The Rate of Mixing of Two-dimensional Markov Shifts - Md. Noorani, Mohd Salmi (Universiti Putra Malaysia Press, 1996)
The definitions of a two-dimensional Markov shift and the associated Markov measure are given. Then a sufficient condition for the exponential mixing of such shifts is provided. This generalizes the well-known result in the one-dimensional case.